Analisis Pengaruh Rasio-rasio Operasi dan Keuangan Tertimbang serta Rasio Persaingan Industri terhadap Kinerja Perusahaan: Studi Empiris Perspektif Internal dan Perspektif Eksternal Organisasi - Ka'aro, Hermeindito (Jurnal Widya Manajemen & Akuntansi, 2001)
This research investigates operating and financial weighted ratios and competitive ratios influencing the three elements of company performance, return on assets, net income growth, and market share. The sample is go-public Indonesian manufacturing company. Data for this study are the financial ratios calculated from financial statements over nine year's period of 1990-1998. Canonical correlation analysis technique is used to examine the effect of some independent variables on three dependent variables simultaneously. Wilks' lambda test will be employed to test the significance of the relationship of them. Research finding show that; first, two of three canonical functions relationship have statistically significant; second, the inventory share and market share are the most importance variables which are contribute to the first functions; third, total assets to sales and return on assets are the most importance variables which are contribute to the second functions; forth, the power of independent variables influencing dependent variables is relatively moderate.